The Problem of Private Language - M.A Abdollahi (Metaphysics, 2014)
The issue of private language entered in the scope of philosophy by Wittgenstein. In his important book, Philosophical Investigations (1953), he argues that the private language is impossible. According to him, the pervious systems of philosophy like Rationalism, Empiricism, Idealism and even Logical Atomism explain the raise of knowledge so that it entails private language. Private language, Wittgenstein defines, is a language whose individual words refer to what can only be known to the speaking person and imply his immediate private sensations. Thus, another person cannot understand the language. This language is, according to Wittgenstein, impossible because it leads to epistemological and semantic skepticism. The definition of private language contains two elements: the âprivacyâ and âreferring toâ. Wittgenstein shows how we may be trapped in solipsism and the only way to avoid this problem is to consider language as a social phenomenon.